Accounting practices and payroll systems of Oxbridge English School : a study on Halishahar Branch - Saimon, Salman Al Azmir Ali (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.